Annual Report Faculty of Business Management 2010 - UiTM, Faculty of Business and Management (Faculty of Business and Management, 2010)
Vision of the faculty to be the best Faculty of Business Management in Malaysia which is of international standard, professional and competitive in terms of teaching, training, research and consultancy and publication. Mission of the faculty : the Faculty of Business Management strives for academic excellence based on quality work culture